Plataformas virtuales y sus metodologías de enseñanza en el ámbito educativo de los estudiantes tercer año de bachillerato de la Unidad Educativa Eugenio Espejo período lectivo 2021-2022 - Rocafuerte Arteaga, Ruth Damaris (2022)
The present case called, "VIRTUAL PLATFORMS AND THEIR TEACHING METHODOLOGIES IN THE EDUCATIONAL FIELD OF STUDENTS IN THE THIRD YEAR OF HIGH SCHOOL OF THE EUGENIO ESPEJO EDUCATIONAL UNIT, CLASS PERIOD 2021-2022", is a case study that deserves all the respective development, it is It is necessary to know the virtual platforms that are currently used, as well as everything related to the methodologies applied to this type of study, so the objective is to analyze these two variables, which allow knowing a little more conceptual information about the use of both. , for this reason, a quantitative research was designed that allows the measurement of these types of variables with better precision, a questionnaire was also developed as a measurement instrument that was applied to the sample of the respective Educational Unit, resulting in the low knowledge that can be obtained conceptually talking about these two variables so important for the current study also Thus, two conclusions were reached, one of a negative nature that indicates that the knowledge that is handled on educational platforms is low for what young people should know, even more so if they are in the online modality, this deficit generates confusion at the educational level and the digital knowledge gap increases and a positive one that maintains that the preferred or best known platforms are Zoom and Microsoft Teams, as a platform that manages virtual education, in the Eugenio Espejo Educational Unit, this aspect is positive because at least in these platforms there is coupling.